Teaching of literature and reading as writing in teacher education: contributions of socio-discursive interactionism - Stutz, Lidia (2019)
Despite advances in the teaching of language and literature since the 1980s, literature has been developed in many schools with different objectives than that of reader´s aesthetic experience. In order to contribute to the equalization of the purposes and means of literature teaching in teacher´s education, this article presents a pathway of the conceptions of reader and reading in the schooling tradition and highlights the contribution of the Sociodiscursive Interactionism for the consideration of reading as writing in the reader´s education.